Genomic and phenotypic characterization of a refactored xylose-utilizing Saccharomyces cerevisiae strain for lignocellulosic biofuel production - Phuong Tran Nguyen Hoang; Ko, Ja Kyong; Gong, Gyeongtaek; Um, Youngsoon; Lee, Sun-Mi (BioMed Central, 2018)
Background: Engineered strains of Saccharomyces cerevisiae have significantly improved the prospects of biorefinery by improving the bioconversion yields in lignocellulosic bioethanol production and expanding the product profiles to include advanced biofuels and chemicals. However, the lignocellulosic biorefinery concept has not been fully applied using engineered strains in which either xylose utilization or advanced biofuel/chemical production pathways have been upgraded separately. Specifically, high-performance xylose-fermenting strains have rarely been employed as advanced biofuel and chemical production platforms and require further engineering to expand their product profiles. Results: In this study, we refactored a high-performance xylose-fermenting S. cerevisiae that could potentially serve as a platform strain for advanced biofuels and biochemical production. Through combinatorial CRISPR-Cas9mediated rational and evolutionary engineering, we obtained a newly refactored isomerase-based xylose-fermenting strain, XUSE, that demonstrated efficient conversion of xylose into ethanol with a high yield of 0.43 g/g. In addition, XUSE exhibited the simultaneous fermentation of glucose and xylose with negligible glucose inhibition, indicating the potential of this isomerase-based xylose-utilizing strain for lignocellulosic biorefinery. The genomic and transcriptomic analysis of XUSE revealed beneficial mutations and changes in gene expression that are responsible for the enhanced xylose fermentation performance of XUSE. Conclusions: In this study, we developed a high-performance xylose-fermenting S. cerevisiae strain, XUSE, with high ethanol yield and negligible glucose inhibition. Understanding the genomic and transcriptomic characteristics of XUSE revealed isomerase-based engineering strategies for improved xylose fermentation in S. cerevisiae. With high xylose fermentation performance and room for further engineering, XUSE could serve as a promising platform strain for lignocellulosic biorefinery.